THE PSYCHOLOGICAL STUDIES OF THE SUSTAINABILITY. APPLICATIONS TO THE TARIFF SYSTEM OF CONSUMER - García Lirios, Cruz (2013)
The purpose of the present article is expose the history, the structures and the applications of the psychological studies around the sustainability of the design of tariff systems of the service of potable water. We are considered two tendencies of the state of the question: conservationism and communitarism. The conservationists’ investigations are analyzed in four structures: validity, covariance, prediction and disturbance. Finally, it provides a synthesis of the conservationists’ investigations for their application in the design of quote systems in the supply and water consumption.